A randomized, controlled trial of raltegravir intensification in antiretroviral-treated, HIV-infected patients with a suboptimal CD4+ T cell response - Hatano, Hiroyu; Hayes, Timothy L; Dahl, Viktor; Sinclair, Elizabeth; Lee, Tzong-Hae; Hoh, Rebecca; Lampiris, Harry; Hunt, Peter W; Palmer, Sarah; McCune, Joseph M; Martin, Jeffrey N; Busch, Michael P; et al. (The Journal of infectious diseases, 2011)
Some human immunodeficiency virus (HIV)-infected individuals are not able to achieve a normal CD4(+) T cell count despite prolonged, treatment-mediated viral suppression. We conducted an intensification study to assess whether residual viral replication contributes to replenishment of the latent reservoir and whether mucosal HIV-specific T cell responses limit the reservoir size. Thirty treated subjects with CD4(+) T cell counts of <350 cells/mm(3) despite viral suppression for ≥ 1 year were randomized to add raltegravir (400 mg twice daily) or matching placebo for 24 weeks. The primary end points were the proportion of subjects with undetectable plasma viremia (determined using an ultrasensitive assay with a lower limit of detection of <.3 copy/mL) and a change in the percentage of CD38(+)HLA-DR(+)CD8(+) T cells in peripheral blood mononuclear cells (PBMCs). The proportion of subjects with undetectable plasma viremia did not differ between the 2 groups (P = .42). Raltegravir intensification did not have a significant effect on immune activation or HIV-specific responses in PBMCs or gut-associated lymphoid tissue. Low-level viremia is not likely to be a significant cause of suboptimal CD4(+) T cell gains during HIV treatment. NCT00631449.